Clinical predictors for walking recovery within six months post stroke: A retrospective cohort study in Thailand - Siriphan Kongsawasdi (2018)
© IOS Press and the authors. All rights reserved. BACKGROUND: Walking difficulty is one of the important neurological consequences after stroke, early prediction of factors related to walking ability may benefit for rehabilitation team to set suitable goals and discharge planning. PURPOSE: This study was performed to identify independent prognostic determinants associated with mobility recovery from ischemic stroke during six months after onset. METHODS: Medical records from first-ever stroke patients who were admitted to the rehabilitation unit were retrospectively reviewed. Baseline characteristics including demographic data, stroke risk factors, motor assessment and stroke-related complications were collected. Outcome measure was ability to walk. To identify clinical predictors, multivariable risk regression analysis was used for analysis. RESULTS: Of a total 146 stroke survivors, 81 patients (55.5) could be independent in walking and 65 (45.5) were non-functional mobility at six months follow-up. Stepwise, multivariable risk regression analysis with generalized linear model demonstrated that follow-up leg score was the strongest independent predictor of walking with risk ratio [RR] of 2.23 (P < 0.01). The association of some stroke-related factors, aphasia and unilateral neglect were found in univariable analysis but revealed no significance from the final model. CONCLUSION: Identification of early predictors associate walking recovery provided meaningful information for stroke care team to consider the amount of care needed and to initiate optimal plan according to realistic goal.